2014
DOI: 10.1111/cdoe.12113
|View full text |Cite
|
Sign up to set email alerts
|

Dental trauma: prevalence and risk factors in schoolchildren

Abstract: The pronounced increase in the prevalence of dental trauma with age highlights the need to establish preventive strategies among schoolchildren. The risk of dental injury was increased in overweight/obese boys and children with histories of dental trauma in early childhood, confirming the existence of accident-prone children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
1
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 37 publications
7
45
1
12
Order By: Relevance
“…Our results are in line with studies among adolescents in Canada 21 and 5-year-olds in Scotland 24 that also found no association between dental trauma and SEP. Similar results were also reported from several studies conducted in low-and middle-income countries such as South Africa 22 and Brazil 20,23,26,31,32 . All these studies used the same criteria for dental trauma as our analysis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results are in line with studies among adolescents in Canada 21 and 5-year-olds in Scotland 24 that also found no association between dental trauma and SEP. Similar results were also reported from several studies conducted in low-and middle-income countries such as South Africa 22 and Brazil 20,23,26,31,32 . All these studies used the same criteria for dental trauma as our analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Brazil) reported that TDI was associated with low SEP [14][15][16][17][18][19] . Finally, some studies found no association between TDI and SEP in either high-, middle-or low-income countries [20][21][22][23][24][25][26] . Very few studies have investigated potential social gradients in TDI; however, the results were conflicting 12,27 .…”
mentioning
confidence: 99%
“…Soccer‐related injuries to the head, face and neck areas represent about 3%‐10% of all soccer‐related injuries . Recent studies estimate that the frequency of soccer‐related oro‐dental injuries among amateur and professional adolescent and adult players was 0.1%‐32% . Still, prevalence studies of soccer‐related TDIs among young amateur players are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization used the motto “Move for Health” in 2002, to emphasize the role of physical activity in the health of mankind . With contact sports in vogue, traumatic dental injuries (TDI) have received epidemiological expression as an emerging public health challenge . TDI can present with disturbing sequelae such as fractured, displaced, or lost teeth.…”
Section: Introductionmentioning
confidence: 99%